Desain pembelajaran matematika realistik yang memanfaatkan sistem sosial masyarakat di Sekolah Menengah Pertama - Usman Mulbar; Ahmad Zaki (Seminar Nasional LP2M UNM, 2019)
This study aims to produce realistic mathematical learning designs that utilize the social system of the community to improve the competence of graduates of junior high school students. This type of research is development research to develop mathematical learning tools that utilize the social system of society. The research subjects were students of the State Middle School in the Province of South Sulawesi. The results showed that the design of mathematical learning models that utilize social systems in junior high schools that meet valid criteria are indicated by the results of expert & practitioner assessment, the practical criteria indicated by the implementation of learning models and abilities the teacher manages learning, the effective criteria indicated by student activity in learning, positive student responses to the implementation of learning, and achievement of individual and classical student learning competencies, Based on the results of student response analysis in learning found that students give positive responses, namely (1) students feel happy about learning activities using the Sismat learning model, learning atmosphere, and the way teachers teach with an average percentage of 98.08%; (2) learning using the Sismat learning model is new for students with an average percentage of 80.29%; (3) shows a very large interest with an average percentage of 100%; and (4) students clearly understand the way teachers teach with an average percentage of 97.69%. The level of competency of student learning outcomes with the Sismat learning model, namely: (1) the results of the learning outcomes competency test, obtained that 88.46% of students obtain a minimum score of 70; and (3) student portfolios meet good criteria, with a mean score of 71.84.